Stress Distribution in 5-Unit Fixed Partial Dentures with a Pier Abutment and Rigid and Nonrigid Connectors with Two Different Occlusal Schemes: A Three-Dimensional Finite Element Analysis - Behnaz Ebadian; Amirhossein Fathi; Shivasadat Tabatabaei (International Journal of Dentistry)
Objectives. This study aimed to assess stress distribution in 5-unit fixed partial dentures (FPDs) with a pier abutment and rigid (RC) and nonrigid connectors (NRCs) with the canine rise and group function occlusal schemes by finite element analysis (FEA). Materials and Methods. In this FEA study, a geometrical model of the maxilla with natural teeth and periodontal ligament (PDL) was three-dimensionally designed and meshed by ANSYS and Pro/Engineer software programs. A 5-unit FPD was then designed to replace the lost first premolar and first molar teeth; the second premolar served as a pier abutment, and the canine and second molar served as terminal abutments. Two FPDs were designed with RC and NRC. Each FPD was analyzed with the canine rise and group function occlusal schemes (a total of 4 models). The first and second molars (180 N), premolars (120 N), and canine (80 N) teeth were subjected to progressive vertical and oblique (12-degree) loads, and maximum von Mises stress and strain in teeth and connectors were calculated for each model. Results. The models had 73704 elements and 137732 nodes. The connector design and occlusal scheme had significant effects on stress distribution in FPDs. The highest von Mises stress (73.035 MPa) was recorded in FPD with RC and group function occlusal scheme. The lowest von Mises stress (0.004 MPa) was recorded in FPD with NRC and canine rise occlusal scheme. Conclusion. Oblique forces created greater stress, and FPD with NRC and canine rise occlusal scheme decreased stress in FPD and increased stress in the tooth crown.